1998
DOI: 10.1063/1.873077
|View full text |Cite
|
Sign up to set email alerts
|

Energy loss of charged projectiles in dusty plasmas

Abstract: The analytical and numerical results for the slowing down of two heavy projectile ions passing through a multicomponent dusty plasma are presented. Within the linear dielectric approach, the electrostatic potential and the stopping power of the two projectiles are computed for different values of KD (the normalized effective wave number) and R (the separation between the two projectiles) retaining two-ion-correlation effects. The enhancement in the energy loss is observed, and it is compared with that of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…We have numerically solved (17) for the ES potential (f) by inserting the dielectric response function from (15) for Krook type collisions and from (16) for BGK type collisions. We then plot f against the normalized axial position x z À V t t for di¡erent values of the test charge velocities with a ¢xed value of the normalized collision frequency n d0 0:2 o pd in Fig.…”
Section: E¡ect Of the Dust-neutral Collision Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…We have numerically solved (17) for the ES potential (f) by inserting the dielectric response function from (15) for Krook type collisions and from (16) for BGK type collisions. We then plot f against the normalized axial position x z À V t t for di¡erent values of the test charge velocities with a ¢xed value of the normalized collision frequency n d0 0:2 o pd in Fig.…”
Section: E¡ect Of the Dust-neutral Collision Frequencymentioning
confidence: 99%
“…Sten£o et al [15] calculated the e¡ect of electron-neutral collisions on the potential of a slowly moving (as compared to the electron thermal motion) test charge by using the BGK collisional model. Later, Nasim et al [16] presented analytical and numerical studies describing the slowing down of heavy charged projectiles in a multi-component dusty plasma but without taking into account dust charge £uctuations. Later they also found that the dust charge £uctuation enhances the energy loss of a test charge in a dusty plasma when the charge relaxation rate is very high and vice versa [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nasim et al 10,11 considered a pair of projectiles and calculated the electrostatic potential and energy loss. They pointed out that the loss or gain of energy of the second projectile depends upon its position relative to the leading projectile.…”
Section: Introductionmentioning
confidence: 99%
“…An important consequence of the potential excited by a moving charge is the energy loss and braking of the velocity due to the resultant electric field at the moving charge. 19,20 The maximum energy exchange occurs for particles at the sonic speed. 21 In the case of multiple test charges, correlation effects distort the potential profile.…”
Section: Introductionmentioning
confidence: 99%